(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Hypertrophic gingivitis is a disease characterized by inflammatory damage to the gums, gradual increase of gingival tissue and the formation of pathological periodontal pockets. In the general structure of periodontal diseases, this pathology accounts for up to 3% of clinical cases. At the same time, women are more often faced with symptomatic manifestations of hypertrophic gingivitis than representatives of the stronger sex.